The CATFISH study protocol: an evaluation of a water fluoridation scheme. Issue 1 (December 2016) - Goodwin, Michaela; Emsley, Richard; Kelly, Michael; Rooney, Eric; Sutton, Matthew; Tickle, Martin; Wagstaff, Rebecca; Walsh, Tanya; Whittaker, William; Pretty, Iain
Abstract Background Tooth decay is the commonest disease of childhood. We have known for over 90 years that fluoride can prevent tooth decay; it is present in nearly all toothpastes and can be provided in mouthwashes, gels and varnishes. The oldest method of applying fluoride is via the water supply at a concentration of 1 part per million. The two most important reviews of water fluoridation in the United Kingdom (the York Review and MRC Report on water fluoridation and health) concluded that whilst there was evidence to suggest water fluoridation provided a benefit in caries reduction, there was a need to improve the evidence base in several areas. Methods/Design This study will use a natural experiment to assess the incidence of caries in two geographical areas, one in which the water supply is returned to being fluoridated following a discontinuation of fluoridation and one that continues to have a non-fluoridated water supply. The oral health of two discrete study populations will be evaluated - those born 9 months after the water fluoridation was introduced, and those who were in their 1st year of school after the introduction of fluoridated water. Both populations will be followed prospectively for 5 years using a census approach in the exposed group along with matched numbers recruitment in a non-exposed control. Parents of the younger cohort will complete questionnaires every 6 months with child clinical examination at ages 3 and 5, whilst the older cohort will have clinical examinations only, at approximately 5, 7 and 11 years old. Discussion This project provides a unique opportunity to conduct a high quality evaluation of the reintroduction of a water fluoridation scheme, which satisfies the inclusion criteria stipulated by the York systematic review and can address the design issues identified in the MRC report. The research will make a major contribution to the understanding of the costs and effects of water fluoridation in the UK in the 21st Century. Its findings will help inform UK policy on this important public health intervention and may have a significant impact on public health policy in other developed countries. There is currently true equipoise in relation to the effectiveness of water fluoridation in contemporary populations and while the biological plausibility is well established, there is a need to examine impact on the changing epidemiological status of dental decay.